2016
DOI: 10.18632/oncotarget.8844
|View full text |Cite
|
Sign up to set email alerts
|

Gli-1/PI3K/AKT/NF-kB pathway mediates resistance to radiation and is a target for reversion of responses in refractory acute myeloid leukemia cells

Abstract: Total body irradiation combined with chemotherapy is currently the most effective procedure as a preparative myeloablative regimen. However, resistance to radiotherapy and chemotherapy in refractory acute myeloid leukemia is associated with short-time recurrence after allogeneic hematopoietic stem cell transplantation. To address this issue, we used three cell lines, HL60, HL60/ADR (adriamycin-resistant cells), and HL60/RX (a radiation-resistant cell line established from HL60 cells), as cellular models to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 43 publications
5
44
0
1
Order By: Relevance
“…The failure in using AKT inhibitors as a single agent for cancer treatment prompted us to test whether they can be applied in combination therapy. In fact, AKT pathway alterations have been implicated in radioresistance in many types of cancer, including head and neck cancer, prostate cancer, glioblastoma, and acute myeloid leukemia [4,9,[21][22][23][24][25][26]. We show that the upregulation of the AKT/S6 signaling axis is the major pathway conferring OSCC cells radioresistance, and inhibiting it significantly reverses the radioresistance in OSCC cells.…”
Section: Discussionmentioning
confidence: 87%
“…The failure in using AKT inhibitors as a single agent for cancer treatment prompted us to test whether they can be applied in combination therapy. In fact, AKT pathway alterations have been implicated in radioresistance in many types of cancer, including head and neck cancer, prostate cancer, glioblastoma, and acute myeloid leukemia [4,9,[21][22][23][24][25][26]. We show that the upregulation of the AKT/S6 signaling axis is the major pathway conferring OSCC cells radioresistance, and inhibiting it significantly reverses the radioresistance in OSCC cells.…”
Section: Discussionmentioning
confidence: 87%
“…Akt/NF-kb signaling pathway is a common signal transduction pathway in eukaryotic cells. It is involved in cell polarity, cell division, proliferation and apoptosis, cell adhesion and migration, and so on (12,13). Related studies confi rmed that the inhibition of TGF-beta upstream protein can effectively inhibit the collagen gel contraction induced by TGFand the expression of type I collagen (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…As overexpression of ErbB was frequently observed in EScc, ErbB may activate the hedgehog and NF-κB pathways to promote EScc progression. A study in refractory acute myeloid leukemia cells reported that inhibition of smoothened homolog, a transducer of the hedgehog pathway, was accompanied by a decrease in the expression of nuclear NF-κB p65 (36). Inhibition of Gli1 by an inhibitor additionally resulted in inactivation of the NF-κB pathway by reducing the phosphorylation levels of NF-κB p65 in TE-8 cells.…”
Section: Discussionmentioning
confidence: 99%